THE CORRELATION BETWEEN ATTITUDE TOWARD ENGLISH TO THE SPEAKING SKILL ON LP3I STUDENTS IN THE ACADEMIC YEAR OF 2016/2017 - Arief Pamuji (Language and Education Journal, 2017)
The objective of this research was to find out whether or not there is a correlation between attitude to the speaking skill. The sample of this research was taken by using total sampling with total 200 students of LP3I Palembang in the academic year 2016/2017. The data were obtained by using questionnaire and speaking test. To verify the hypotheses, the primary data were analyzed by using correlation and regression analyses by means of Statistical Product and Service Solution (SPSS) version 12.00 computer program. Based on the data analysis, the correlation coefficient (rxy) was 0.633 at the significance level p< 0.05 in two-tailed. Since the value of r-obtained was higher than the critical value of r-table (0.633 >0.1388), the null hypothesis (Ho) was rejected and consequently, the research hypothesis (H1) was accepted. This shows a significant correlation between attitude to the speaking skill on LP3I students Palembang in the academic year 2016 - 2017. And from R2 (the coefficient determiner) was 0.40, it meant that attitude influenced was 40 % of their speaking skill and the rest (60 %) was defined by other factors. It means that there was a significant influence of attitude on the students’ speaking skill